Impaired Oxygenation of the Prefrontal Cortex During Verbal Fluency Task in Young Adults With Major Depressive Disorder and Suicidality: A Functional Near-Infrared Spectroscopy Study - Kim, Hyewon; Choi, JongKwan; Jeong, Bumseok; Fava, Maurizio; Mischoulon, David; Park, Mi Jin; Kim, Hyun Soo; Jeon, Hong Jin (Frontiers in Psychiatry, 2022)
Background: Few previous studies have focused on prefrontal activation in young adults diagnosed with MDD and suicidality via fNIRS. Methods: A total of 59 healthy controls (HCs), 35 patients with MDD but without suicidality and 25 patients with MDD and suicidality, between the ages of 18–34 years, were enrolled. Changes in oxygenated hemoglobin (oxy-Hb) levels of the prefrontal cortex at baseline, 4 weeks, and 8 weeks, were evaluated using a protocol consisting of three consecutively repeated trials of rest, speech, and verbal fluency test (VFT) via fNIRS. MDD was diagnosed and suicidality was evaluated based on Mini International Neuropsychiatric Interview (MINI). Results: Oxy-Hb levels were impaired in patients with MDD compared with HCs (p = 0.022 for left prefrontal cortex; p = 0.037 for right orbitofrontal cortex; p = 0.009 for left frontopolar cortex). Among the three groups including HCs, MDD without suicidality, and MDD with suicidality, prefrontal oxygenation was most decreased in MDD patients with suicidality. A significantly impaired prefrontal oxygenation in the right ventrolateral prefrontal cortex (VLPFC) was detected after adjusting for covariates in MDD patients with suicidality, compared to those without suicidality. Conclusions: Impaired prefrontal oxygenation during cognitive execution may serve as a diagnostic biomarker for suicidality in young adult patients with MDD.